An In Vitro Model of Gastric Inflammation and Treatment with Cobalamin - T. R. Elliott; A. L. Guildford (International Journal of Inflammation)
Pernicious anaemia (PA) is an autoimmune condition where antibodies target intrinsic factor and parietal cells, reducing the patient’s ability to absorb cobalamin promoting atrophic gastritis. Treatment guidelines are based on excretion data of hydroxocobalamin from healthy individuals obtained 50 years ago. This manuscript describes the use of phorbol 12-myristate 13-acetate (PMA) to stimulate low grade inflammation in an epithelial colorectal cell line to assess the efficacy of methylcobalamin and hydroxocobalamin. Nitric oxide increased significantly in cells exposed to higher doses of PMA (100 ng/ml, 150 ng/ml, and 200 ng/ml) accompanied by a loss of the characteristic cobblestone morphology with no negative effect on cell activity or viability. A significant reduction in nitric oxide production was associated with the addition of 200 pg/ml hydroxocobalamin, alongside a return to the characteristic cobblestone morphology. This study highlights the use of PMA to promote low grade inflammation in human cell lines to model gastric inflammation associated with autoimmunity; furthermore it raises questions regarding the concentration of cobalamin administered clinically to restore cell functionality, feasibly allowing the patient to receive reduced quantity of the vitamin more regularly, providing the patient with levels which are akin to dietary intake.